英会話教室のテレビ CM と日本人英語学習者 - Inoue Miyuki (MEDIA, ENGLISH AND COMMUNICATION, 2019)
This study analyzes the advertisements of English conversation schools to investigate the discourse of English-speaking skills promotion in Japan. Especially, it examines TV advertisements of three leading English schools: AEON, ECC, and NOVA. The analysis utilizes Multimodal Critical Discourse Analysis (MCDA) (Machin & Mayr, 2012) to critically examine linguistic and visual semiotic choices. It seeks to reveal ideologies and power relations embedded in the advertisements that seem neutral and normal on the surface. The analysis reveals that the advertisements present that if people can speak English they can gain certain experiences and certain feelings as well. Additionally, it finds that the advertisements emphasize the two categories of Japanese: those who can speak English and those who cannot. They are ranked in a hierarchy. Japanese who can speak English are represented in a better position of influence. 本研究では、日本の英会話教室における英会話促進に関するディスコースを検証するため、大手英会話教室の AEON、 ECC、 NOVAのテレビ CM3本を分析する。本研究が適用する理論の枠組みは、主にマルチモダル批判的談話分析(Multimodal Critical Discourse Analysis, MCDA) (Machin & Mayr, 2012)である。テレビ CMで使われた言語及び視覚イメージをそれぞれ分析しながら、一見自然で中立的なイデオロギーと権力の関係を明らかにする。結果として、英語が話せることでその他の体験や感情をも手に入れることが可能だというイデオロギー的な考えが明らかとなった。また、英語が話せる日本人と話せない日本人二つの区別された表象が作り上げられ、序列化されている。そこでは英語が話せる日本人は僅位な立場に位置付けられ、権力が付与されている。